Maxillary molars in class II, derotate or distalize: A Systematic review - Yasmina El HONSALI; Hajar BEN MOHIMD; Fatima ZAOUI; Abdelali HALIMI (University of Mosul, College of Dentistry, 2023)
Aims: This review aims to prove whether derotation can correct minimal class II. Materials and Methods: The systematic search included Medline (PubMed, Ovid MEDLINE and EBSCO, Science Direct, and Cochrane Library (Cochrane Review, Trails), and additional studies were searched in the reference lists of all articles. The date of the last search was December 13th, 2022. The methodological quality of the retrospective studies was graded by means of the Quality Assessment Tool for Quantitative Studies, developed for the Effective Public Health Practice Project (EPHPP), and prospective studies by means of the Newcastle-Ottawa Scale. Results: Totally, 1342 studies were identified for screening, and 5 studies were eligible. The Quality Assessment Tool for Quantitative Studies rated 2, of the included retrospective clinical studies as high risk and 1 as moderate risk. The Newcastle- Ottawa Scale rated all 2 included studies as high risk. The mean molar derotation values varied from 1 mm to 2 mm. Conclusion: Through this systematic review, we have highlighted that; the derotation can correct the minimal class II. It is possible thanks to several devices like traspalatin arch, clear aligner, headgear, and some distalizers especially those with vestibular action. The mean molar derotation values varied from 1 mm to 2 mm, conditionally to not lose the space obtained by the effect of mezialization